THE ROLE OF EDUCATIONAL EVENTS IN THE COOPERATION OF FAMILY, SCHOOL, COMMUNITY IN PROTECTING DISADVANTAGED STUDENTS FROM ALIEN IDEOLOGIES - Akram Sultanov (International Scientific and Current Research Conferences, 2021)
The article emphasizes the role of the media in protecting children with disabilities from various spiritual and ideological threats in formulating national ideas in collaboration with schools, families and communities